Transcriptomics Study on Staphylococcus aureus Biofilm Under Low Concentration of Ampicillin - Liu, Junyan; Yang, Ling; Hou, Yuchao; Soteyome, Thanapop; Zeng, Bingbing; Su, Jianyu; Li, Lin; Li, Bing; Chen, Dingqiang; Li, Yanyan; Wu, Aiwu; Shirtliff, Mark E.; et al. (Frontiers in Microbiology, 2018)
Staphylococcus aureus is one of the representative foodborne pathogens which forms biofilm. Antibiotics are widely applied in livestock husbandry to maintain animal health and productivity, thus contribute to the dissemination of antimicrobial resistant livestock and human pathogens, and pose a significant public health threat. Effect of antibiotic pressure on S. aureus biofilm formation, as well as the mechanism, remains unclear. In this study, the regulatory mechanism of low concentration of ampicillin on S. aureus biofilm formation was elucidated. The viability and biomass of biofilm with and without 1/4 MIC ampicillin treatment for 8 h were determined by XTT and crystal violet straining assays, respectively. Transcriptomics analysis on ampicillin-induced and non-ampicillin-induced biofilms were performed by RNA-sequencing, differentially expressed genes identification and annotation, GO functional and KEGG pathway enrichment. The viability and biomass of ampicillin-induced biofilm showed dramatical increase compared to the non-ampicillin-induced biofilm. A total of 530 differentially expressed genes (DEGs) with 167 and 363 genes showing up- and down-regulation, respectively, were obtained. Upon GO functional enrichment, 183, 252, and 21 specific GO terms in biological process, molecular function and cellular component were identified, respectively. Eight KEGG pathways including “Microbial metabolism in diverse environments”, “Staphylococcus aureus infection”, and “Monobactam biosynthesis” were significantly enriched. In addition, “beta-lactam resistance” pathway was also highly enriched. In ampicillin-induced biofilm, the significant up-regulation of genes encoding multidrug resistance efflux pump AbcA, penicillin binding proteins PBP1, PBP1a/2, and PBP3, and antimicrobial resistance proteins VraF, VraG, Dlt, and Aur indicated the positive response of S. aureus to ampicillin. The up-regulation of genes encoding surface proteins ClfB, IsdA, and SasG and genes (cap5B and cap5C) which promote the adhesion of S. aureus in ampicillin induced biofilm might explain the enhanced biofilm viability and biomass.